PENGARUH ETOS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RADIO LA NUGRAHA 105 FM PALEMBANG - Herman Efrizal; Suharti . (JURNAL KOMPETITIF, 2018)
This researche studies the correlation among Work Ethics , Discipline And Simultaneous Partial Work in the Employee Performance At La Nugraha 105 Fm Radio Palembang.The population in this study are employees of Radio La Nugraha Fm 105 Palembang totaling 30 employees. Samples in this study of 30 respondents, where by using saturation sampling technique (Census). Keywords: Work Ethics, Discipline Work, Employee Performance